Disparitas Sanksi Administratif Akibat Keterlambatan Pemberitahuan Pengambilalihan Saham Pelaku Usaha Berdasarkan Hukum Persaingan Usaha - Nastity, Sally Dian; Adam, Richard C. (Syntax Literate, 2023)
This study investigates disparities in the application of administrative sanctions due to late notification of takeover of business actors based on competition law. This phenomenon is important because of its impact on business competition order and fairness in economic law enforcement. Normative legal research is a research method in the field of law that focuses on the analysis of legal texts and legal documents in order to understand, interpret and evaluate the legal framework that regulates a particular legal problem or problem. The results showed a significant disparity in law enforcement related to the delay in notification of the takeover. Factors such as regulatory policies, level of awareness of business actors, and legal interpretation play a key role in determining the level of sanctions imposed.